Ecuador - Crisis, Poverty and Social Services (Vol. 2 of 2) : Annexes - World Bank (Washington, DC, 2013)
Over the past decade, Ecuador has suffered natural disasters, political instability, and financial crises. These events have occurred in the context of already low economic growth and high income inequality and poverty and have exposed the poor to the risk of irreversible losses of assets, including human capital. This paper updates our knowledge of poverty in Ecuador. Chapter 1 describes the high poverty and income inequality in Ecuador, and how both poverty and inequality have been increasing in recent years. Chapter 2 describes the current crisis, the effect of the crisis on the poor and the near-poor, and Government stabilization in response to the crisis. Chapter 3 focuses on the provision of basic public services of nutrition, health, and education to the poor. Chapter 4 reviews those public sector programs specifically targeted on the poor. It begins with the Bono Solidario, and then reviews programs that benefit each of the especially vulnerable groups among the poor. It ends with an assessment of social infrastructure program which have the potential to generate employment. Chapter 5 examines policy options to provide income support, to prevent irreversible physical and mental losses and losses in human capital. Finally, Chapter 6 estimates the cost of implementing the strategy discussed in the previous chapters, and assesses the possibilities of financing the strategy within the Government's expected social sector resource envelope.